Adopsi media sosial oleh pemerintah: studi kasus akun TikTok kementerian keuangan - Setyorini, Endah (Jurnal Studi Komunikasi, 2022)
The use of social media as a communication medium for organisations, including by government agencies, is a practice that is considered more efficient than traditional media. One of the social media that has been widely used in the last two years is TikTok. This article describes the process of adopting TikTok as a new communication medium for the government and its management strategy. The study focused on the @kemenkeuri account owned by the Ministry of Finance, which is one of the best government institutions in the field of Government Public Relations (GPR) in Indonesia. Data were obtained through interviews with @kemenkeuri’s administrators and through observations on the TikTok@kemenkeuri account page. The results of the study indicate that the adoption of TikTok by the Ministry of Finance is currently still in its second stage, which according to the Mergel & Bretschneider (2013) model is referred to as the “Order from Chaos” stage.